The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/1464592
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-Automated Usability Evaluation Framework for Interactive Image Segmentation Systems

Abstract: For complex segmentation tasks, the achievable accuracy of fully automated systems is inherently limited. Specifically, when a precise segmentation result is desired for a small amount of given data sets, semi-automatic methods exhibit a clear benefit for the user. The optimization of human computer interaction (HCI) is an essential part of interactive image segmentation. Nevertheless, publications introducing novel interactive segmentation systems (ISS) often lack an objective comparison of HCI aspects. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…There is a need to identify methods that are able to quickly assess hundreds or thousands of design possibilities and rank them similarly to how they would be with a human data driven tool such as SUS. Some work in this direction has been done within very specific contexts, such as usability evaluation of new interfaces for image segmentation systems, such as those used to identify anomalies in medical scans (Amrehn, et. al.…”
Section: Human Voice and Assessing Usabilitymentioning
confidence: 99%
“…There is a need to identify methods that are able to quickly assess hundreds or thousands of design possibilities and rank them similarly to how they would be with a human data driven tool such as SUS. Some work in this direction has been done within very specific contexts, such as usability evaluation of new interfaces for image segmentation systems, such as those used to identify anomalies in medical scans (Amrehn, et. al.…”
Section: Human Voice and Assessing Usabilitymentioning
confidence: 99%
“…In a study by Amrehn et al, 23 it was concluded that interactive segmentation methods are beneficial for complex structures as opposed to fully automated segmentation methods that inherently lack domain knowledge.…”
Section: Introductionmentioning
confidence: 99%